Genderization In Automobile Industry In Recruitment & Selection: Examining the Impact of Genderization in Recruitment and Selection in the Automobile Industry (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The purpose of this paper is to give an overallassessment of Recruitment &Selection practices in automobile industry, (An Empirical study with specialreference to gender issues). The Automobile industry in India is todaycaught in a vortex of rapid ramp-up of production, sales, lean manufacturingand cost-cutting initiatives coupled with an unusual restlessness and churn inhuman assets. It is passing through a critical phase of increasing complexitiesand quantum changes. Further, the need to align with global best practices,while managing strategic priorities and uncertain government policies requiresa realignment of talent matrices.